Neck cooling provides ergogenic benefits after heat acclimation during exercise in the heat - Zhang, Guangxia; Xin, Guangjie; Li, Haicheng; Ma, Pengwei; Wang, Haoyan (Frontiers in Physiology, 2025)
BackgroundBoth heat acclimation and neck cooling have been shown to alleviate heat stress and may help maintain exercise performance in the heat. However, no previous research has been determined their combined effects on thermal perception and physiological responses during exercise in the heat.ObjectiveTo determine the effects of neck cooling applied before and after heat acclimation on physiological responses, thermal perceptions, and time to exhaustion exercise performance in the heat.MethodsFourteen non-heat acclimated men completed a randomized crossover design, involving 10 consecutive days of heat acclimation exercise (HAE) in a controlled heat chamber (35 °C, 30%RH). Participants performed four time-to-exhaustion tests (TTE) with neck cooling (NC) or without (CON) before (Pre-NC and Pre-CON) and after HAE (Post-NC and Post-CON). The TTE test comprised an initial 30 min incremental phase (starting at 50%VO2max, increasing 5% every 5 min) followed by a constant workload phase at 70%VO2max until volitional exhaustion. Temperature from tympanic membrane (Ttym) and neck (Tneck), heart rate (HR), ratings of perceived exertion (RPE), thermal comfort (TC), thermal acceptability (TA), and thermal sensation (TS) were recorded at 5 min interval.ResultsFollowing 10 days of HAE, participants exhibited a significant increase in local sweat rate (p = 0.002), and reductions in sweat sodium concentration (p = 0.04) and HR (p = 0.02). TTE performance exhibited significant main effects for both cooling (p = 0.003) and HAE (p = 0.002), while the interaction effect approached significance (p = 0.069). Comparing to the Pre-CON trial, the Post-NC had a significantly greater percentage improvement in TTE (17.3% ± 13.5%) than Pre-NC (3.4% ± 9.9%, p = 0.01) and Post-CON (4.9% ± 13.0%, p = 0.03). Moreover, thermal perception measures revealed significant main effects of cooling (TC: p = 0.01; TS: p < 0.001; TA: p = 0.003) and significant interaction effects (TC: p = 0.036; TS: p = 0.004; TA: p = 0.048), with the Post-NC exhibiting significantly improved TC and reduced TS compared to other groups.ConclusionNeck cooling provides ergogenic effects in thermal perceptions and extends a greater improvement in time to exhaustion performance when applied after heat acclimation. These findings suggest that individuals should achieve physiological adaptation to the heat before neck cooling is introduced for perceptual or performance benefits.